التنمية المهنية لأعضاء هيئة التدريس بمؤسسات التعليم العالي في ليبيا: الواقع وآفاق المستقبل - البدري, عبد الرحيم محمد (Scientific Journal of University of Benghazi, 2019)
Human resources are the backbone of any university، college، or specialized institute. Qualified and dedicated staff are the key to ensure that higher education institutions fulfill their mission of teaching، learning، research، and society service. The focus of this research is the reality and expecting future of professional development policies and practices of higher education institutions in Libya. The main objectives of this study are to increase the awareness and understanding of importance of professional development for teaching، and research abilities for all staff members especially the new staff ones. Therefore، it is very beneficial for the Libyan higher education system to prepare professional development programmers to rise their; knowledge in teaching، research and administrative side. They should assure that these educators have a decisive voice at every stage of planning، implementation and evaluating students' achievement. This depends on supporting and educating the whole students. To have high standards for students، there must be high standards for staff members too who work with them. Finally، the researcher presents some recommendations، for improving competence of staff members in Libyan higher education institutions to raise their abilities in different areas such as teaching، research and administration.